Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Essai français, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»--Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres